Controlled fabrication of hierarchical WO3·H2O hollow microspheres for enhanced visible light photocatalysis. Issue 21 (4th February 2015) - Guo, Sheng-Qi; Zhen, Meng-Meng; Sun, Mei-Qing; Zhang, Xiao; Zhao, Ya-Ping; Liu, Lu
Abstract : A new type of hierarchical WO3 ·H2 O hollow microsphere, whose formation was successfully controlled based on the reaction system for preparing simple nanoplates, showed excellent photocatalytic activity for the degradation of dye under visible light. Abstract : WO3 ·H2 O nanostructures have been prepared through a facile hydrothermal route by controlling their morphology during synthesis. WO3 ·H2 O nanoplates with a thickness of ∼45 nm and hierarchical hollow microspheres (HMSs) structures could be obtained by introducing different amounts of citric acid. X-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM) were employed to understand the structure and morphology of the two types of WO3 ·H2 O. The formation mechanisms for WO3 ·H2 O nanoplates and WO3 ·H2 O HMSs were investigated. The photocatalytic activities, determined by rhodamine B (RhB) degradation under visible light irradiation of WO3 ·H2 O HMSs photocatalysts, were significantly improved as compared with WO3 ·H2 O nanoplates. The higher efficiency of photocatalytic activity in WO3 ·H2 O HMSs was attributed to its higher surface-to-volume ratio and stability against aggregation. In addition, we investigated the toxicity of WO3 ·H2 O HMSs against an important model fungus, yeast ( Saccharomyces cerevisiae ). The results indicate that the as-synthesized hierarchical WO3 ·H2 O HMSs could be used as a green and efficient photocatalyst.